Pharmacists' strategies to detect, resolve, and prevent DRPs in CKD patients - Ni Made Susilawati; Eli Halimah; Siti Saidah (Pensoft Publishers, 2021)
Pharmacists have undergone obstacles in the process of detecting, resolving, and preventing CKD patients' DRPs. Thus, optimal strategies were needed. A total of 19 articles were included based on the article searching process. Based on the articles, it can be concluded: The strategies of detecting DRPs in CKD patients were carried out through medication reconciliation and medication review. The outcomes of these strategies were the number of DRPs/patients and types of DRPs detected. Strategies to resolve and prevent DRPs in CKD patients were conducted through interprofessional collaboration, education, and counselling. The outcome of these strategies was a change in the patients' DRPs status. Optimization of detection, resolution, and prevention strategies were performed by improving pharmacists' professional hard and soft-skills as well as modifying the pharmaceutical care delivery model. A decrease in the number of DRPs/patients and a change in DRPs status were reported as the outcomes of optimizing this process.